Dynamic responses of sandwich cemboard-foamed concrete panels subjected to low-velocity impact - Z. M., Jaini; Shahrul Niza, Mokhatar; Hadipramana, J.; Mazrul Nizam, Abu Seman (IOP Publishing, 2019)
Sandwich cemboard-foamed concrete panel (SCFCP) has sparked the attention due to green and sustainability requirements in construction of building. SCFCP is essentially made of fiber cement board as core component and foamed concrete as outer layers. Shear connectors act as joint mechanism and create compositeness behaviour. However, investigations on SCFCP remains passive, creating a number of uncertainties particularly in dynamic responses. Therefore, this study intends to investigate the dynamic responses of SCFCP under low-velocity impact. Nine cube specimens were prepared using size of 100 mm x 100 mm x 100 mm, while nine panel specimens were casting using size of 1220 mm x 300 mm x 76 mm. The compression and impact tests were conducted on cube and panel specimens. The compression test revealed that foamed concrete has compressive strength approximately 18 MPa with density of 1600 kg/m3 . Under low-impact of 1.39 m/s, it is noticeable that the impact force decreases from 8.41 kN to 6.73 kN in correspond to the spacing of shear connector. Contradictory, the displacement shows sprang off pattern with value between 87.90 mm to 96.50 mm.